Increased Prevalence, Complications, and Costs of Smokers Undergoing Total Knee Arthroplasty - Rajaee, Sean S.; Debbi, Eytan M.; Paiement, Guy D.; Spitzer, Andrew I. (The Journal of Knee Surgery, 2020)
Given a national push toward bundled payment models, the purpose of this study was to examine the prevalence as well as the effect of smoking on early inpatient complications and cost following elective total knee arthroplasty (TKA) in the United States across multiple years. Using the nationwide inpatient sample, all primary elective TKA admissions were identified from 2012 to 2014. Patients were stratified by smoking status through a secondary diagnosis of “tobacco use disorder.” Patient characteristics as well as prevalence, costs, and incidence of complications were compared. There was a significant increase in the rate of smoking in TKA from 17.9% in 2012 to 19.2% in 2014 (p < 0.0001). The highest rate was seen in patients < 45 years of age (27.3%). Hospital resource usage was significantly higher for smokers, with a length of stay of 3.3 versus 2.9 days (p < 0.0001), and hospital costs of $16,752 versus $15,653 (p < 0.0001). A multivariable logistic model adjusting for age, gender, and comorbidities showed that smokers had an increased odds ratio for myocardial infarction (5.72), cardiac arrest (4.59), stroke (4.42), inpatient mortality (4.21), pneumonia (4.01), acute renal failure (2.95), deep vein thrombosis (2.74), urinary tract infection (2.43), transfusion (1.38) and sepsis (0.65) (all p < 0.0001). Smoking is common among patients undergoing elective TKA, and its prevalence continues to rise. Smoking is associated with higher hospital costs as well as higher rates of immediate inpatient complications. These findings are critical for risk stratification, improving of bundled payment models as well as patient education, and optimization prior to surgery to reduce costs and complications.
Keywords: smoking; total knee arthroplasty; prevalence; complications; cost